MULTILAYER COMPOSITE PLASMA COATINGS ON SCREEN PROTECTION ELEMENTS BASED ON ZIRCONIUM DIOXIDE - V. A. Okovity; F. I. Panteleenko; V. V. Okovity; V. M. Astashinsky; P. P. Hramtsov; M. Y. Cernik; V. V. Uglov; V. I. Chimanskiy; N. N. Cerenda; S. B. Sobolewski (Наука и техника)
The paper contains results of investigations pertaining to an influence of plasma jet parameters (current, spraying distance, consumption of plasma formation gas (nitrogen)), fractional composition of initial powder and degree of cooling with compressed air on anti-meteoric coating characteristics. Optimum modes (arc current 600 A; spray distance of 110 mm; consumption of plasma formation gas (nitrogen) – 50 l/min; fractional composition of zirconium dioxide powder <50 μm; compressed air consumption for cooling – 1 m3/min; p = 4 bar) make it possible to obtain anti-meteoric coatings based on zirconium dioxide with material utilization rate of 62 %, total ceramic layer porosity of 6 %. After exposure of compression plasma flows on a coating in the nitrogen atmosphere a cubic modification of zirconium oxide is considered as the main phase being present in the coating. The lattice parameter of cubic zirconium oxide modification is equal to 0.5174 nm. Taking into consideration usage of nitrogen as plasma formation substance its interaction with zirconium coating atoms occurs and zirconium nitride (ZrN) is formed with a cubic crystal lattice (lattice parameter 0.4580 nm). Melting of pre-surface layer takes place and a depth of the melted layer is about 8 μm according to the results of a scanning electron microscopy. Pre-surface layer being crystallized after exposure to compression plasma flows is characterized by a homogeneous distribution of ele-ments and absence of pores formed in the process of coating formation. The coating structure is represented by a set of lar- ge (5–7 μm) and small (1–2 μm) zirconium oxide particles sintered against each other. Melting of coating surface layer and speed crystallization occur after the impact of compression plasma flows on the formed coating. Cracking of the surface layer arises due to origination of internal mechanical stresses in the crystallized part. While using a scanning electron microscopy a detailed analysis of the surface structure has permitted to reveal a formation of a cellular structure with an average cell size of less than 1 μm in the crystallized portion and formation of the cells can be caused by speed crystallization of the melted layer.